El Semillero Infantil del Carnaval De Riosucio y La Labor De Salvaguardar Y Difundir La Tradición Del Carnaval (2014)
The central purpose of this work is the study of the children's nursery of the Riosucio Caldas carnival. Specifically, the investigation here presented pursues the purpose of revealing a fundamental pedagogical initiative which is part of a special plan to safeguard the carnival, created with the in order to manage, protect and disseminate all the tradition and identity of the people of Riosucio that is present in the cultural manifestation of the carnival.